2002
DOI: 10.1111/j.1749-6632.2002.tb04645.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolus and Apoptosis

Abstract: The nucleolus represents a highly dynamic nuclear compartment of the interphase nucleus. It plays a key role in ribosome biogenesis. The number of nucleoli, their size, and their activity increase in exponentially growing cells; therefore these parameters reflect the proliferating activity of the cells. A variety of staining techniques have been employed to vizualize nucleolar changes in malignant cells. Staining of so-called nucleolar organizer regions (NORs), based upon a strong avidity of nucleolar proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 22 publications
(24 reference statements)
4
41
0
2
Order By: Relevance
“…Nucleolus plays important roles in cell apoptosis (45). Inhibition of rRNA synthesis in cancer cells is known to cause nucleolar stress that results in disintegration of nucleoli (46).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolus plays important roles in cell apoptosis (45). Inhibition of rRNA synthesis in cancer cells is known to cause nucleolar stress that results in disintegration of nucleoli (46).…”
Section: Discussionmentioning
confidence: 99%
“…Inside the nucleus, the nucleolus is the most prominent structure. Owing to the difference in density between nucleolus and its surrounding nucleoplasm (0.215 g/cm 3 versus 0.106 g/cm 3 ), known for a long time but recently determined by the refractive indices in the nucleus of Xenopus oocytes [1], the nucleolus is easily observed in monolayer culture cells under a phase-contrast microscope ( Figure 1A). It appears as an oval to round shape but varies in sizes and numbers in different types of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, a larger size and higher number of nucleolus are detected in the most tumor cells than in the corresponding normal cells. Therefore, abnormal sizes and higher numbers of nucleoli are commonly used as indicators for many cancers in prognosis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Rubbi and Milner (2003) have recently proposed that the nucleolus is a stress sensor capable of maintaining the levels of p53 within an acceptable range: in their model, the level of p53 goes up as soon as nucleolus function is impaired. In this view, nucleolus (and nucleolar proteins) could be seen as the Praetorian guard of the nuclear homeostasis.Since the first papers it has been reported that the nucleolus exhibits striking changes during apoptosis, undergoing segregation eventually leading to disappearance (Kerr et al, 1972;Wyllie et al, 1980;Horky et al, 2002). In fact this is not completely true; the complex structure of the nucleolus is disrupted and segregation of its dense fibrillar component (DFC) and granular component (GC) occurs (Fig.…”
mentioning
confidence: 99%